The Moderating of Government Public Policy on Housing Purchase Decisions in Tasikmalaya - Ade Komaludin; Dodi Tirtana; Dedi Rudiana (AIBPM Publisher, 2024)
The housing industry is experiencing an increase in demand, especially subsidized housing. Various factors are the main considerations for consumers in determining purchasing decisions such as environment, green open space, price, and location. The object of this research is 4 subsidized housing in Tasikmalaya Regency. This model measures government public policy as a moderating in deciding to buy a subsidized house. This study uses primary data in the form of a Likert scale questionnaire to measure each variable. The sample determination technique uses Proportionate Stratified Random Sampling. This research method uses SEM - PLS (Structural Equation Modeling - Partial Least Square). The results showed that government policy has a moderating role for the environment on housing purchase decisions. Environmental, green open space and price have a direct impact on purchasing decisions. The implication of this finding will be the establishment of supporting facilities related to the location of subsidized housing. In this case the government needs to ensure that public facilities are available before the subsidized housing project is implemented.